The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13013-018-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional and structural leg length discrepancy in patients with adolescent idiopathic scoliosis using the EOS imaging system: a prospective comparative study

Abstract: BackgroundTo our knowledge, no studies have reported the exact structural leg length discrepancies (LLDs) in patients with adolescent idiopathic scoliosis (AIS). Therefore, this study aimed to evaluate the differences between functional and structural LLDs and to examine the correlations between LLDs and spinopelvic parameters in patients with AIS using an EOS imaging system, which permits the three-dimensional reconstruction of spinal and lower-limb bony structures.MethodsEighty-two consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 24 publications
(16 reference statements)
2
38
0
Order By: Relevance
“…The functional LLDs appeared to be correlated with lumbar Cobb angles but not thoracic Cobb angles 14) . This suggested that functional LLD is possibly compensatory to lumbar curves.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…The functional LLDs appeared to be correlated with lumbar Cobb angles but not thoracic Cobb angles 14) . This suggested that functional LLD is possibly compensatory to lumbar curves.…”
Section: Resultsmentioning
confidence: 80%
“…They found that structural LLDs were not common in AIS patients as opposed to functional LLDs. Of the cohort, none had structural LLD in excess of 10 mm, whereas 18 of them had functional LLD in excess of 10 mm 14) .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations